Workshop Implementasi Bimbingan Dan Konseling Dalam Kurikulum Merdeka Dan Penyusunan Perangkat Pembelajaran (LPPM Universitas HKBP Nommensen, 2024)
A guidance and counseling teacher is a figure who supports the smoothness of the learning process in school. Through their duties, guidance and counseling teachers are required to develop their competencies through innovation and curriculum development. In order to enhance their competencies, a workshop on the implementation of guidance and counseling within the